ANALYSIS OF THE EFFECT OF EXPOSURE TO CHLORPYRYPHOS, CARBOFURAN, AND CYPERMETHRIN ON SPERMATOGENESIS IN ADOLESCENT RAT - Janu, Libri Wira Indra; Wahyudi, Septa Surya; Sofiana, Kristianningrum Dian (Indonesian Journal of Urology, 2023)
Objective: To investigate the effect of exposure to chlorpyryphos, carbofuran, and cypermethrin on spermatogenesis in adolescent rat. Material & Methods: This study is an experimental study with a post-test only control group design. In this study, 30 adolescent rats aged 30-45 days were randomly divided into 5 groups. Group I was a normal control or without treatment for 21 days (K0), group II was a solvent control group, namely DMSO 5% which was administered subcutaneously for 21 days (KI), group III was a group that received chlorpyrifos 20 mg/kgBW dissolved with DMSO 5% subcutaneously for 21 days (P1), group IV was the group that received carbofuran 0.2 mg/kgBW dissolved with DMSO 5% subcutaneously for 21 days (P2), group V was the group that received cypermethrin 20 mg/kg. kgBW dissolved with 5% DMSO subcutaneously for 21 days (P3). Ipsilateral testicular orchidectomy was performed on all rats to remove the left testicular organ for preparation with Haematoxylin Eosin staining. The spermatogenesis score was calculated based on the Johnsen score in 5 seminiferous tubule visual fields. Data were analyzed using Kruskal Wallis followed by Mann Mitney test. The difference was considered significant at p<0.05. Results: There was a significant decrease in spermatogenesis scores between P1, P2, and P3 against K0 and K1 (p<0.05). On the other hand, there was no significant difference in the decrease in spermatogenesis scores between P1 and P2, P1 and P3, P2 and P3 and K0 and K1 (p>0.05). Conclusion: Exposure to chlorpyrifos, carbofuran, and cypermethrin had an effect on reducing spermatogenesis scores in adolescent rats.